2012
DOI: 10.1093/carcin/bgs391
|View full text |Cite
|
Sign up to set email alerts
|

Daxx regulates mitotic progression and prostate cancer predisposition

Abstract: Mitotic progression of mammalian cells is tightly regulated by the E3 ubiquitin ligase anaphase promoting complex (APC)/C. Deregulation of APC/C is frequently observed in cancer cells and is suggested to contribute to chromosome instability and cancer predisposition. In this study, we identified Daxx as a novel APC/C inhibitor frequently overexpressed in prostate cancer. Daxx interacts with the APC/C coactivators Cdc20 and Cdh1 in vivo, with the binding of Cdc20 dependent on the consensus destruction boxes nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…Furthermore, its ectopic expression in a non-malignant prostate epithelial cell line induced polyploidy under mitotic stress. Daxx may promote chromosome instability during prostate cancer development [12]. So it implies Daxx might play a critical role in the cellular transformation and cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, its ectopic expression in a non-malignant prostate epithelial cell line induced polyploidy under mitotic stress. Daxx may promote chromosome instability during prostate cancer development [12]. So it implies Daxx might play a critical role in the cellular transformation and cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…One study has shown that Daxx, an APC inhibitor, interacts with Cdc20 and inhibits the degradation of APC Cdc20 substrates, leading to a transient delay in mitotic progression and chromosome instability (Kwan et al, 2013). Consistently, Daxx is overexpressed in prostate cancer tissues and positively correlated with the Gleason score and metastasis (Kwan et al, 2013). Moreover, LATs (L-type amino acid transporters) protein was expressed at all stages of prostate cancer.…”
Section: Role Of Cdc20 In Human Malignanciesmentioning
confidence: 99%
“…In prostate tissues, DAXX staining intensity is stronger in areas surrounding tumor glands compared to areas surrounding normal glands [16]. Moreover, strong positive DAXX staining has been observed in PCa tissues, compared to benign prostatic hyperplasia (BPH) tissues, suggesting that DAXX is overexpressed in PCa [17]. In prostate cells, DAXX levels are increased in various PCa cell lines, relative to nontumorigenic human prostatic epithelial lines [17; Submitted].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, strong positive DAXX staining has been observed in PCa tissues, compared to benign prostatic hyperplasia (BPH) tissues, suggesting that DAXX is overexpressed in PCa [17]. In prostate cells, DAXX levels are increased in various PCa cell lines, relative to nontumorigenic human prostatic epithelial lines [17; Submitted]. Conversely, in cells and tissues, DAPK1 and DAPK3 are downregulated in cancer contexts [18; Submitted].…”
Section: Introductionmentioning
confidence: 99%